Metodologia para quantificação e avaliação da partição de agrotóxicos no estuário do Rio Jaguaribe-Ce - Lima, Danielle Monteiro de (2011)
Hydrochemical conditions, as well as the physical and chemical properties of pesticides, are closely linked to the dynamics of pesticides, adsorption and have an impact on their toxicity and bioavailability, and fate in the environment. The present work aims to improve a simple and plausible analytical method for determination of pesticides picloram, atrazine, methyl parathion, chlorpyrifos and cypermethrin, contributing to a better understanding of these pesticides behavior in the partition between the dissolved and particulate fraction, as well as the governing parameters. The chromatographic techniques used, such as gas chromatography-mass spectrometry (GC-MS) and Gas Chromatography with Flame Ionization Detector (GC-FID) showed satisfactory results presented in the analytical figures of merit. The limit of detection ranged from 0.07 to 0.63 μg/L using GC-MS and from 11.38 to 116.00 μg/L using GC-FID, and chromatographic methods showed precision and satisfactory coefficients of correlation. The method of selective Liquid Liquid Extraction (ELL-s), which, using 30 mL of extracting mixture hexane/dichloromethane/ethyl acetate (1:1:1, v/v), was efficient for the extraction of pesticides studied. The recovery results were better in the synthetic samples (Milli-Q water) with concentration of 50 mg.L-1 than in environmental samples (water from the estuary of river Pacoti), which showed a lower recovery efficiency, this decrease being influenced by matrix effect, manifested by the presence of interfering extracts from environmental sample. The evaluation of the partition of pesticides parathion, chlorpyrifos and atrazine between dissolved and particulate fractions showed that fluvial and estuarine environments in these partitions are differentiated and influenced by hydrochemical conditions and dependent on physico-chemical pesticides investigated